The role of skin biopsy in the detection of exposure to endocrine disrupting chemicals in Mediterranean cetaceans - FOSSI, MARIA CRISTINA; MARSILI, LETIZIA; NOTARBARTOLO DI SCIARA G. (2003)
Use of skin biopsy is proposed as a sensitive non-lethal technique for the hazard assessment of Mediterranean cetaceans exposed to endocrine disrupting chemicals (EDCs). EDCs afe a structurally diverse group of compounds that may adversely affect the health of humans and wildlife or their progeny, by interaction with the endocrine system. In the Mediterranean environment top predators accumulate high concentrations of polyhalogenated aromatic hydrocarbons (PHAHs) and toxic metals, incurring high toxicological hazard. In this paper, the hypothesis that Mediterranean cetaceans afe potentially at risk due to PHAH-EDCs is investigated using skin biopsy samples. Benzo-cx-pyrene monoxigenase (BPMO) activity in skin biopsies was used as a potential indicator of exposure to different organochlorines (OCs) known to have endocrine disrupting properties. The main objective of this paper was to use this non-destructive ecotoxicological tool to deCine the potential hazard to Mediterranean odontocete and mysicete species, comparing the present data with values detected in other cetaceans from heavily polluted areas, affected by pseudohermaphroditism and other reproductive dysfunction. Subcutaneous tissue consisting of skin and blubber was obtained from striped dolphins (Stenella coeruleoalba) , bottlenose dolphins (Tursiops truncatus), common dolphins (Delphinus delphis) and fin whales (Balaenoptera physalus) in the Mediterranean basino Sampling was performed in the western Ligurian Sea, between Corsica and the French-Italian coast, and in the Ionian Sea. High concentrations of DDT metabolites and PCB congeners (known as Endocrine Disruptors) were detected in the different species. Significant differences in BPMO induction and OC levels were found between odontocetes and mysticetes. Differences in organochlorine bioaccumulation and consequently potential risk due to endocrine disruptors were primarily related to different positions in the marine food web. A statistical correlation was found between BPMO activity and ...